STUDI LITERATUR: PERAN GURU KELAS DALAM MENGATASI KESULITAN BELAJAR ANAK SLOW LEARNER DI SEKOLAH DASAR - Jagat Satria Roziqin; Qothrun Nada; Rahmalia Intan Bardilah; Anggi Citra Apriliana; Taofik (STKIP Subang, 2024)
This research was conducted with the aim of finding out the development and feasibility of Relay Smart Card media with addition and subtraction material for class I elementary schools. This type of research is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects of this research were 23 students at SDN Setiabudi 01. The results of the development in the form of Relay Smart Card learning media, based on the results of the media expert's assessment of the material, language and media implementation, stated that all three were in the very feasible category. And, for the one to one, small group, field test and questionnaire assessment scores by the teacher, good scores were obtained. The results from the assessment of student and teacher response questionnaires were that the one to one trial response results obtained a percentage of 77%, the small group trial response results obtained a percentage of 84%, the field test response results obtained a percentage of 91% and the teacher's response obtained a percentage of 87%. with an average percentage of around 80%. So from these results it can be concluded that the relay smart card learning media is suitable for use by students.